2004
DOI: 10.2337/diacare.27.11.2622
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Inhaled Insulin (Exubera) Compared With Subcutaneous Insulin Therapy in Patients With Type 1 Diabetes

Abstract: OBJECTIVE -The aim of this study was to determine whether premeal pulmonary delivery of rapid-acting, dry-powder insulin (Exubera) plus Ultralente could provide glycemic control comparable to a conventional insulin regimen in type 1 diabetes.RESEARCH DESIGN AND METHODS -Three hundred thirty-five subjects were randomly assigned to receive either premeal inhaled insulin plus bedtime Ultralente or two to three injections of regular and NPH insulin for 24 weeks. The primary end point was a change in HbA 1c . RESUL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
221
2
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(236 citation statements)
references
References 14 publications
9
221
2
4
Order By: Relevance
“…These findings are analogous to and complement those of recent studies comparing inhaled and conventional subcutaneous insulin regimens in type 1 and type 2 diabetes (12,21). It should be noted that in our study and others, the insulin dosages probably were not always maximized, despite subjects' not achieving protocol target values.…”
Section: Safety and Tolerabilitysupporting
confidence: 74%
See 2 more Smart Citations
“…These findings are analogous to and complement those of recent studies comparing inhaled and conventional subcutaneous insulin regimens in type 1 and type 2 diabetes (12,21). It should be noted that in our study and others, the insulin dosages probably were not always maximized, despite subjects' not achieving protocol target values.…”
Section: Safety and Tolerabilitysupporting
confidence: 74%
“…Results of a proof-of-concept study have suggested that inhaled insulin could replace preprandial subcutaneous insulin injections in type 1 diabetic subjects (10,11). A larger study demonstrating that inhaled insulin can provide glycemic control comparable with that of conventional subcutaneous insulin has reinforced this idea (12). Our study investigated whether a basal/ bolus insulin regimen involving premeal inhaled, rapid-acting, dry-powder insulin plus twice-daily subcutaneous neutral protamine Hagedorn (NPH) insulin could provide comparable glycemic control comparable with that achieved with a basal/bolus subcutaneous insulin regimen of premeal regular insulin plus twice-daily NPH insulin in type 1 diabetic subjects.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Recently, a series of multicenter trials of inhaled human insulin (Exubera [insulin human (rDNA origin)] Inhalation Powder; Pfizer, Inc., New York, NY; and Nektar Therapeutics, San Carlos, CA) was completed in individuals with type 1 and 2 diabetes (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Serial DL CO measurements were obtained in participants receiving inhaled insulin and in comparator participants receiving no inhaled therapy.…”
mentioning
confidence: 99%
“…At the end of the 6-month trial, HbA 1 c was similar in the two treatment groups, and fasting plasma glucose (FPG) was 1.3 mmol/l lower in the Exubera/ultralente group [1]. At first sight, it seems that the different basal insulins could explain the lower FPG in the Exubera/ultralente group.…”
Section: Abbreviations Fpg: Fasting Plasma Glucosementioning
confidence: 97%